A Practical Comprehensive Approach to Management of Acute Decompensated Heart Failure - Nwosu, Chukwunweike; Mezue, Kenechukwu; Bhagatwala, Kunal; Ezema, Nonso (Current Cardiology Reviews, 2016)
Heart failure (HF) has a high incidence and prevalence in the USA and worldwide. It is a very common cause of significant morbidity and mortality with serious cost implications on the US health sector. The primary focus of this review is to synthesize an effective comprehensive care plan for patients in acute decompensated heart failure (ADHF) based on the most current evidence available. It begins with a brief overview of the pathophysiology, clinical presentation and evaluation of patients in ADHF. It then reviews management goals and treatment guidelines, with emphasis on challenges presented by diuretic resistance and worsening renal function (WRF). It provides information on recognition of advanced HF even during acute presentation, estimation of prognosis and proactive identification of patients that will benefit from mechanical cardiac devices, transplantation and palliative care/hospice. In addition, it presents strategies to address the problem of readmissions, which is an ominous prognostic factor with enormous economic burden.
Keywords: ADHF